Physicochemical, antioxidant capacity, and sensory properties of bligo juice (Benicasa hispida) with bligo peel extract addition - Dini Nur Hakiki; Athiefah Fauziyyah; Sri Wijanarti; Nabila Aisya Putri Pribadi; Nur Hidayah (jurnal1, 2022)
This study aimed to develop bligo juice as functional food by adding Bligo Peel Extract (BPE) with concentrations of 1%, 2%,and 3%. The characteristics of bligo juice before and after BPE addition were investigated by proximate analysis, examination of total solids, viscosity, vitamin C, and antioxidant capacity, and sensory evaluation. Results showed that BPE addition increased the vitamin C levels, antioxidant activity, carbohydrates, fats, and acceptance of color, flavor, and viscosity of bligo juice but decreased its acceptance of taste and acceptability. The addition of 1% BPE provided the highest acceptance rate compared with other variations. In summary, BPE addition increases the vitamin C, antioxidant activity, and carbohydrate content of bligo juice, thus improving its health benefits.